2020
DOI: 10.3390/s20174928
|View full text |Cite
|
Sign up to set email alerts
|

Neckio: Motivating Neck Exercises in Computer Workers

Abstract: Neck pain is common among computer workers who may spend too much time in a static posture facing their display. Regular breaks and variety in one’s posture can help to prevent discomfort and pain. In order to understand how to support computer workers to do so regularly, we surveyed a convenience sample of computer workers (N = 130) regarding their work habits and their attitudes towards neck exercises at the workplace. The survey showed that they are highly motivated, but not able to comply with a neck exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 38 publications
0
3
0
1
Order By: Relevance
“… 21 In a study of individuals who work on a computer for over six hours a day, 35.9% did not engage in neck exercises. 22 A study conducted in Greece found that those who engaged in deep neck flexor muscle workouts had a reduction in levels of anxiety and despair. 23 Other research suggests that exercises to enhance flexibility and strengthen neck muscles may positively affect depression, stress, and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“… 21 In a study of individuals who work on a computer for over six hours a day, 35.9% did not engage in neck exercises. 22 A study conducted in Greece found that those who engaged in deep neck flexor muscle workouts had a reduction in levels of anxiety and despair. 23 Other research suggests that exercises to enhance flexibility and strengthen neck muscles may positively affect depression, stress, and anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Educational campaigns to raise awareness about proper smartphone ergonomics and posture could be beneficial [ 13 ]. Additionally, incorporating regular breaks and exercises to alleviate tension and strain may help reduce the incidence of these symptoms [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…From the employer's perspective, in order to prevent the aforementioned phenomena, the implementation of preventive and rehabilitative measures at the early stage of musculoskeletal overload was crucial [10,11]. Neck and/or shoulder pain negatively affected the limbs used by an employee to operate a computer, both in terms of static and dynamic work [12,13]. Therefore, an important element of diagnostic activities is the objective assessment of the function of the aforementioned limb as a "specific link" between the employee and the computer, especially during arm movements similar to those performed when using a computer [14].…”
Section: Introductionmentioning
confidence: 99%